Penerapan Pembelajaran Hybrid pada Mata Pelajaran Pembuatan Sulaman Aplikasi di SMK Negeri 2 Jombang - Yulianti Puspa Rini; Inty Nahari; Deny Arifiana; Mein Kharnolis (Journal on Education, 2024)
The hybrid learning model is one of the learning that can be applied to the basic competencies of making application embroidery in a product. This learning model is one of the alternative learning models during the COVID-19 pandemic. The objectives of this study are: 1.) To find out the hybrid learning process in the subject of making application embroidery, 2.) To find out the results of applying hybrid learning in the subject of making application embroidery, 3.) To find out the learning outcomes of making application embroidery after applying hybrid learning. The type of research used is descriptive quantitative with a research design One-shot case study design conducted in class XI Busana-4 SMK Negeri 2 Jombang. Method of data collection by observation. The implementation of the hybrid learning model on basic competencies makes application embroidery show excellent quality